Topological modes in one-dimensional solids and photonic crystals. - Atherton, Timothy J.; Butler, Celia A. M.; Taylor, Melita C.; Hooper, Ian R.; Hibbins, Alastair P.; Sambles, Roy.; Mathur, Harsh. (Tufts University. Tisch Library., 2017)
It is shown theoretically that a one-dimensional crystal with time-reversal and particle-hole symmetries is characterized by a topological invariant that predicts the existence or otherwise of edge states. This is confirmed experimentally through the construction and simulation of a photonic crystal analog in the microwave regime. It is shown that the edge mode couples to modes external to the photonic crystal via a Fano resonance.